Design and characterization of hybrid III–V concentrator photovoltaic–thermoelectric receivers under primary and secondary optical elements. (15th September 2018) - Sweet, T.K.N.; Rolley, M.H.; Li, W.; Paul, M.C.; Johnson, A.; Davies, J.I.; Tuley, R.; Simpson, K.; Almonacid, F.M.; Fernández, E.F.; Knox, A.R.
Highlights: Novel integration of III:V concentrator photovoltaic cells-thermoelectric modules. Optimized thermoelectric module geometry for cell temperature sensing and cooling. New III:V triple-junction cell six-parameter one-diode equivalent model developed. The model fitted experimental current–voltage data with a low 4.44% mean error. High combined primary & secondary optical intensity gain coefficient 0.92 obtained. Abstract: Lattice-matched monolithic triple-junction Concentrator Photovoltaic cells (InGa(0.495) P/GaIn(0.012) As/Ge) were electrically and thermally interfaced to two Thermoelectric Peltier module designs. An electrical and thermal model of the hybrid receivers was modelled in COMSOL Multiphysics software v5.3 to optimize cell cooling whilst increasing photon energy conversion efficiency. The receivers were measured for current–voltage characteristics with the cell only (with sylguard encapsulant), under single secondary optical element at x2.5 optical concentration, and under Fresnel lens primary optical element concentration between x313 and x480. Measurements were taken in solar simulators at Cardiff and Jaén Universities, and on-sun with dual-axis tracking at Jaén University. The hybrid receivers were electrically, thermally and theoretically investigated. The electrical performance data for the cells under variable irradiance and cell temperature conditions were measured using the integrated thermoelectric module as both a temperature sensor and as a solid-state heat pump. The performance of six hybrid devices were evaluated within two 3-receiver strings under primary optical concentration with measured acceptance angles of 1.00° and 0.89°, similar to commercially sourced Concentrator Photovoltaic modules. A six-parameter one-diode equivalent electrical model was developed for the multi-junction cells under both primary and secondary optical concentration. This was applied to extract six model parameters with the experimental current–voltage curves of type A receiver at 1, 3 and 500 concentration ratios. Standard test conditions (1000 W/m 2, 25 °C and Air Mass 1.5 Global spectrum) were assumed based on trust-region-reflective least squares algorithm in MATLAB. The model fitted the experimental current–voltage curves satisfactorily with a mean error of 4.44%. The combined primary and secondary optical intensity gain coefficient is as high as 0.92, in comparison with 0.50–0.86 for crossed compound parabolic concentrators. The determined values of diode reverse saturation current, combined series resistance and shunt resistance were similar to those of monocrystalline PV cell/modules in our previous publications. The model may be applicable to performance prediction of multi-junction CPV cells in the future.